An epimer of threose nucleic acid enhances oligonucleotide exonuclease resistance through end capping - Junlin Wen; Chunlei Zhang; Xue Chen; Ziwen Dai; Mengting Li; Wenjian Ma; ChiYung Yam; Xiaoluo Huang; Chenghe Xiong; Hui Mei (Communications Chemistry)
Abstract End capping of oligonucleotides by modified nucleotides is essential for boosting resistance to 3’ exonuclease degradation, thereby enhancing their stability and therapeutic efficacy in vivo. However, the rationale behind these modifications remains unclear. In this study, we designed a novel nucleic acid analog, eTNA, by replacing deoxyribose with the α-D-erythrofuranosyl moiety. As an epimer of TNA (threose nucleic acid), it combines structural features from inverted-dT and TNA, both known for enhancing resistance against 3’-exonucleases. On top of this, we systematically investigated the stability of a series of oligonucleotides capped with inverted-dT, TNA and eTNA at the 5’-, 3’-, or both ends. The structural differences between eTNA and natural dT help to understand how the sugar ring’s conformation and rigidity affect duplex stability and exonuclease resistance. Our experimental and theoretical results show that the modified furanose affects the binding positions of terminal nucleotides in the phosphodiesterase active site, preventing phosphodiester hydrolysis. Our mechanistic study should benefit future therapeutic oligonucleotide design with end capping.